Bauman's Sociology and Some Basic Concepts (8gen-ART, 2022)
Zygmunt Bauman, one of the leading figures of contemporary sociologists, is also a person who, as a Jew born in Poland at the end of the first quarter of the twentieth century, lived an important part of world political history. He is an important thinker both for his century and for twenty-first century social sciences. Bauman based his sociology on this idea, starting from the idea that postmodernity can be interpreted as 'modernity that failed to realize its original plan'. Bauman is of the opinion that the modern mind's effort to organize and classify societies causes racism and cultural assimilation. According to Bauman, those who make this effort are the political administration and the intellectuals. With these criticisms, Bauman declares that modernity is in crisis. Bauman's views, most of which are based on these criticisms of modernity, extend to the postmodern understanding. Bauman does not clearly present a comparison of modernity - postmodernity in his works, but states that the understanding of the day is not the same as the modern understanding allows these distinctions to be noticed. In addition, the phenomena of modernity, ambiguity, modern genocide and alienation occupy an important place in his books. These concepts and facts, which Bauman has analyzed in detail, are included in the scope of the study.Bauman's works and articles written about him constitute the main source of the study. In addition, in this study, it is aimed to reveal the main theoretical and conceptual framework of Bauman's understanding of sociology.
Keywords: Holocaust; Modernity; Postmodernity; Stranger; Zygmunt Bauman